PWE-029 Characterisation and Association of Abdominal Pain With Anxiety or Depression in Patients with Irritable Bowel Syndrome with Constipation (IBS-C). (4th June 2013) - Quigley, E M; Lavins, B; Shiff, S J; Shi, K; Hao, X; Kurtz, C; Currie, M; Schneier, H; Johnston, J
Abstract : Introduction: The Short-Form McGill Pain Questionnaire (SF-MPQ-2) assesses and characterises pain. It consists of 22 items (rated from 0 = none to 10 = worst possible) in 4 subscales (continuous pain, intermittent pain, neuropathic pain [sensory descriptors], and affective descriptors [emotional aspects of pain, eg cruel/exhausting]). The SF-MPQ-2 has not yet been validated in abdominal pain and, therefore, its use in functional gastrointestinal disorders like IBS is limited. Also, little is known about pain quality in IBS. We used the SF-MPQ-2 to characterise baseline abdominal pain in IBS-C and to determine whether subscale scores were associated with significant baseline anxiety or depression. Methods: Over a 2-wk baseline period in 2 Phase 3 trials of linaclotide (LIN), patients (pts) with IBS-C (Rome II criteria; N = 1523) rated daily their worst abdominal pain over the past 24 h on an 11-point scale (0 = none, 10 = very severe) and completed the SF-MPQ-2. Summary statistics were calculated for each SF-MPQ-2 item and subscale. Pts were grouped by their highest-scored pain subscale and the pain subscale reported by the highest % of pts was defined as the predominant pain type. Association of each subscale with baseline abdominal pain score was determined by ANCOVA. Baseline anxiety and depression were assessed on the Hospital Anxiety and Depression Scale (HADS-A and HADS-D); pts were categorised as normal/borderline (0–10) or abnormal (11–21). Association of each subscale with abnormal HADS was analysed by logistic regression. Results: Continuous pain was the predominant pain type (77% of pts); the item with the highest average score in this subscale was cramping pain. Baseline abdominal pain score was significantly associated with McGill continuous pain (p < 0.0001), intermittent pain (p = 0.004) and affective descriptors (p = 0.012), but not with neuropathic pain (p = 0.526). Only the affective descriptors subscale was significantly associated with abnormal HADS score (Table). Conclusion: These data indicate that continuous pain is predominant in IBS-C and that anxiety and depression are related to the emotional response to pain, not to pain itself. Support: Ironwood Pharmaceuticals Inc & Forest Laboratories Inc. Editing: CMC funded by Almirall Disclosure of Interest: E. Quigley Speaker bureau with: Danone, Janssen, Procter and Gamble, sanofi-aventis, Shire and Yakult, Conflict with: Advisory boards for Almirall, Ironwood, Janssen, Norgine, Salix and Shire/Movetis, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, S. Shiff Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, K. Shi Employee of: Forest Laboratories, X. Hao Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, C. Kurtz Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, H. Schneier Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals